Extracellular vesicles secreted by human gingival mesenchymal stem cells promote bone regeneration in rat femoral bone defects - Wang, Situo; Liu, Ziwei; Yang, Shuo; Huo, Na; Qiao, Bo; Zhang, Tong; Xu, Juan; Shi, Quan (Frontiers in Bioengineering and Biotechnology, 2023)
Extracellular vesicles (EVs), important components of paracrine secretion, are involved in various pathological and physiological processes of the body. In this study, we researched the benefits of EVs secreted by human gingival mesenchymal stem cells (hGMSC-derived EVs) in promoting bone regeneration, thereby providing new ideas for EVs-based bone regeneration therapy. Here, we successfully demonstrated that hGMSC-derived EVs could enhance the osteogenic ability of rat bone marrow mesenchymal stem cells and the angiogenic capability of human umbilical vein endothelial cells. Then, femoral defect rat models were created and treated with PBS, nanohydroxyapatite/collagen (nHAC), a grouping of nHAC/hGMSCs, and a grouping of nHAC/ EVs. The results of our study indicated that the combination of hGMSC-derived EVs and nHAC materials could significantly promote new bone formation and neovascularization with a similar effect to that of the nHAC/hGMSCs group. Our outcomes provide new messages on the role of hGMSC-derived EVs in tissue engineering, which exhibit great potential in bone regeneration treatment.